Cylindrical excavations in overconsolidated clays supported by jet grout walls: analysis considering the consolidation effect - José Leitão Borges (2011)
Using a computer program based on the finite element method, a cylindrical excavation in an overconsolidated clay, supported by a jet-grout wall, is analysed. The computer code incorporates the BiotŽs consolidation theory (coupled formulation of the equilibrium and flow equations) with soil constitutive relations simulated by the p-q- critical state model. Particular attention is given, during and after the construction period, to the analysis of the excess pore pressure, stress levels and displacements in the soil, as well as of the circumferential compression stresses, bending moments, displacements and earth pressures on the wall.